PRINSIP DAN GAYA HIDUP WARIA DALAM KARYA LUKIS - Ardi Rahmad, Jupriani, Yasrul Sami (Universitas Negeri Padang, 2013)
Waria constitutes someone that has to be not accord among physical, phisics, and seks in mean physically she is male but psychologically female, to is not accord that happening makes waria discontented to its genital organ and wants to change it, to back up that change, therefore waria gets behaviour and identification her as female as. This opus resultant pass various processes and there are many inspired of experience those are felt while face or chum and meets a waria in alone writer life. There is wish even writer as creator is so that opus gets meaning by whom only.On opus draws this writer features is Expressionist. Its materializes this opus of yielding observing, kontemplasi, then visualisation into lines, color and desirable object form. Opus that writer features to be backed up by marks sense tool and material, then aiming to artistic problem that becomes elements on each opus.Keywords: Waria, Style, and Physically